Distribution characteristics of size-fractionated Chlorophyll a in the coastal area of the Leizhou Peninsula in winter - Xu, Huabing; He, Mingming; Liao, Jianzu; Zhou, Weihua (Frontiers in Marine Science, 2024)
The distribution characteristics of size-fractionated Chlorophyll a (Chl-a) and the environmental factors were studied in the coastal area of Leizhou Peninsula in January 2022. The result showed that Chl-a ranged from 0.39 to 4.78 mg/m 3 (averaging 1.21 mg/m 3 ) at the surface and 0.43 to 2.78 mg/m 3 (averaging 1.04 mg/m 3 ) at the bottom layer, respectively. The spatial distribution of Chl-a concentration was associated with salinity. High Chl-a concentration was observed in the eastern part of the Leizhou Peninsula characterized by lower salinity, and low Chl-a concentration in Qiongzhou Strait with higher salinity. Nanophytoplankton (2-20 µm) was the dominant contributor, accounting for 61.3% and 63.7% of the total Chl-a at the surface and bottom layer, respectively. Both microphytoplankton (>20 µm) and nanophytoplankton displayed increased Chla with the increase in total Chl-a. Salinity, nutrients and temperature appear to influence the phytoplankton size structure in the coastal area of Leizhou Peninsula. Additionally, the regulation of nutrient varied among phytoplankton of different sizes. This study contributed to our understanding of coastal ecosystem processes and has potential implications for coastal management and monitoring efforts.